Sistem Informasi Klinik Berbasis Web untuk Pengelolaan Data Pasien dan Konsultasi secara Realtime di Klinik Perawatan Weiku - Mohamad Farhat; Triana Harmini; Miftahuddin Fahmi (Prosiding, 2025)
Klinik Weiku is a healthcare institution that still employs a manual management system, which poses potential risks of data loss and difficulties in data retrieval. This study aims to develop a web-based information system for patient data management and real-time medical consultations by applying the Waterfall development model, which consists of the stages of planning, analysis, design, implementation, testing, and maintenance. The main features of this system include online patient registration and real-time consultation services with medical professionals, with three types of users: doctors, who can view and respond to patient messages; nurses, who manage registration data; and patients, who can register and consult online. The technologies used include ReactJS for the user interface (front-end), NodeJS and ExpressJS for the server side (back-end), and MongoDB as the database, with JavaScript as the primary programming language. The system was evaluated through four testing methods: blackbox testing, media expert testing, material expert testing, and user testing. The results show that all features functioned as planned, with material expert testing achieving an average score of 93.33%, media expert testing 91.11%, and user testing 95.0%. Based on these results, the system is deemed feasible for use as a web-based information system for patient data management and real-time consultation services at Klinik Weiku